Global, regional, and national metabolic risk factors associated with multiple myeloma, 1990-2021: analysis via the global burden of disease study 2021 - Zhang, Guozhi (Frontiers in Oncology, 2025)
Background and objectivesThis study aimed to examine the global disease burden of multiple myeloma (MM) linked to metabolic factors. Using data from GHDx spanning 1990–2021, MM cases were identified via ICD-10 codes (C90.0). Key metrics, including mortality rate and disability-adjusted life years (DALYs) rate, were analyzed; age-standardized rates (ASMR, ASDR) and estimated annual percentage change (EAPC) were computed using R to compare disparities across regions, genders, and age groups.Methods and data sourcesThirty-one years of data from GHDx were utilized to capture temporal trends. MM cases were coded according to ICD-10 (C90.0), and age-standardized rates were applied to reduce demographic biases. Temporal changes were assessed via EAPC, while differences across regions, genders, and age groups were analyzed through comparisons of ASMR and ASDR.Key findingsFrom 1990 to 2021, global deaths from metabolic-related MM tripled, with DALYs increasing by 2.8 times. Mortality rates, ASMR, and ASDR showed significant upward trends—slowing between 2000 and 2010 before rebounding. Males exhibited higher ASDR and ASMR, attributed to lifestyle factors and estrogen-mediated protection in females. Middle-SDI countries saw sharp increases in ASDR (driven by population aging and limited healthcare access), whereas High-SDI countries exhibited slower growth (due to advanced treatment options). Most regions recorded rising ASDR, except in high-income Asia Pacific and North America (attributed to novel therapeutic agents). The United States, China, and Germany recorded the highest number of deaths (linked to population size and aging), while countries such as the Bahamas had elevated rates. Underdeveloped regions grappled with underdiagnosis problems. Age-specific analysis showed a rising burden among those aged 70–74 years and older, with elderly males being the most affected group in 2021.ConclusionsThe global burden of metabolic-related MM is shaped by demographic factors, economic conditions, lifestyle, and healthcare provision. High-risk groups (elderly males, Middle-SDI countries, and regions with poor metabolic health) necessitate tailored, region-specific prevention strategies.